ESTETIKA (International journal of artificial intelligence, 2026)
This article provides a scientific analysis of the philosophical and theoretical foundations, historical development, and contemporary directions of aesthetics as an academic discipline. The study examines the evolution of aesthetic thought from antiquity to the present day, the principal categories of aesthetics (the beautiful, the sublime, the tragic, the comic, and the ugly), the dialectical relationship between art and reality, and the new aesthetic conceptions of the twentieth and twenty-first centuries. Special attention is devoted to the contribution of Central Asian thinkers — al-Farabi, Ibn Sina, al-Biruni, and Alisher Navoi — to Eastern aesthetics. The research applies theoretical-analytical, comparative-historical, hermeneutic, and synthesis methods. The findings demonstrate that aesthetics is not only an integral part of art studies but also a vital component of humanity’s spiritual culture, playing a decisive role in the moral development of the individual and in shaping the aesthetic consciousness of society.